THE STUDY ASSIGNMENT AGREEMENT IN THE PERSPECTIVE OF DISPUTE AGREEMENTS AND RESOLUTIONS - Indriyo, St. Mahendra Soni; Christiani, Th. Anita; Prasetiyo, Reinardus Budi (Justitia et Pax, 2020)
The legal issues in this study are aimed to determine the legal provisions for returning compensation to Yayasan Slamet Riyadi Yogyakarta (YSRY) in an overseas study assignment agreement. Furthermore, this study is to determine and analyze the dispute resolution efforts that best provide a sense of justice for both parties. This research is a normative juridical that uses secondary data and uses qualitative data analysis and deductive conclusion techniques. The results show that First, there is a need for material and good faith guarantees from employees who carry out the assignment agreements. Second, non-litigation efforts need to be done in addition to a litigation effort undertaken by YSRY.